Use of fibrin sealant in prevention of hanging palate: A rare complication after cleft palate surgery - Veena Singh; Arun K Singh; Vijay Kumar (Wolters Kluwer Medknow Publications, 2015)
Dehiscence of the mucoperiosteal flap from the alveolar margin is one of the rare complications reported after cleft palate surgery. This situation has been termed a "hanging palate". [1] In these cases, secondary suturing is bound to fail. Intraoperative use of adhesives can obviate this problem. Although the adhesion system cannot and should not replace surgical suture, it provides valuable assistance in tissue synthesis and in local hemostasis at the time of primary surgery, particularly in cases where conventional suture methods are difficult to apply. In addition to good adhesion and good tissue compatibility, the adhesive is completely absorbed. This paper emphasizes on the effectiveness of the fibrin glue for the prevention of such a complication.